Closed doors and the risen Christ : sermons and reflections on being a Christian - Abraham, K. C.; St. Mark's (Parish : Bangalore, India) (Bangalore : Asian Trading Corp., 2007)
Selection of sermons preached at St. Mark's Cathedral, Bangalore, a church under the Church of South India.
Keywords: Church of South India -- Sermons; Sermons, English -- India -- Bangalore